2003
DOI: 10.1073/pnas.0630649100
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of paired claudin strands within apposing plasma membranes

Abstract: The tight junction (TJ) strand is a linear proteinaceous polymer spanning plasma membranes, and each TJ strand associates laterally with another TJ strand in the apposing membranes of adjacent cells to form ''paired'' TJ strands. Claudins have been identified as the major constituents of TJ strands, and when exogenously expressed in L fibroblasts, they polymerize into paired strands, which are morphologically similar to paired TJ strands in epithelia. Here, we show that a fusion protein of GFP with claudin-1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
177
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(195 citation statements)
references
References 35 publications
18
177
0
Order By: Relevance
“…37 Co-culture of HeLa cells expressing different claudin genes revealed that while CLDN1 and CLDN5 were heterotypically interacting with CLDN3, they would not heterotypically bind to CLDN4, demonstrating considerable selectivity in heterotypic claudin-claudin interactions. 38 39 FRAP studies suggest that claudin molecules assembled in tight junctions have limited mobility, 40 consistent with their known heteromeric interactions with scaffold proteins in the tight junction.…”
Section: Claudin-claudin Interactionmentioning
confidence: 84%
“…37 Co-culture of HeLa cells expressing different claudin genes revealed that while CLDN1 and CLDN5 were heterotypically interacting with CLDN3, they would not heterotypically bind to CLDN4, demonstrating considerable selectivity in heterotypic claudin-claudin interactions. 38 39 FRAP studies suggest that claudin molecules assembled in tight junctions have limited mobility, 40 consistent with their known heteromeric interactions with scaffold proteins in the tight junction.…”
Section: Claudin-claudin Interactionmentioning
confidence: 84%
“…Furthermore, it is not clear that the same molecular pathway is utilized by ions as opposed to larger molecules. Interestingly, when claudins are exogenously expressed in fibroblasts, the dynamic behavior of the polymerized paired strands can be observed (49). Biochemical analysis of claudin-4 produced in insect cells revealed a labile nature of the claudin oligomer, implying a dynamic state (39).…”
Section: Discussionmentioning
confidence: 99%
“…As compared to occludin, the endothelial-specific the tight junction protein claudin-5 did not appear to be susceptible to degradation by MMP-2 or MMP-9 under the conditions of these experiments. Although an exact role for occludin in the function of tight junctions has not been fully established, it is postulated that occludin has some role in stabilizing claudin oligomers 11 as well as regulating the activity of the cytoskeleton with various signaling pathways in the cell. 4 A recent study has demonstrated that the addition of peptides corresponding to a portion of the occludin extracellular domain caused increased permeability in cells as measured by TER.…”
Section: Discussionmentioning
confidence: 99%